Faktor Penghambat Pelaksanaan Bimbingan Konseling Kelompok di SMP PAB 10 Medan Estate - Harahap, Ade Chita Putri; Surbakti, Fitri Br; Linri, Linri; Miranda, Miranda; Nadila, Olga Rizki; Lubis, Septi Aulia; Siregar, Sri Intan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Group guidance and counseling is one of the important services provided in schools. However, at SMP PAB 10 Medan Estate, the implementation of group guidance and counseling faces several obstacles. The aim of this research is to identify and analyze the inhibiting factors that affect the implementation of group guidance and counseling at SMP PAB 10 Medan Estate. This research uses a qualitative approach with data collection techniques through interviews and observations. The results of the study show that there are several inhibiting factors that affect the implementation of group guidance and counseling at SMP PAB 10 Medan Estate, including lack of support from the school, lack of knowledge and skills of the BK teachers, and lack of student participation and motivation. Keywords: Group Guidance And Counseling, Inhibiting Factors, SMP PAB 10 Medan Estate.